A Proposed Modified Proportional Fairness Scheduling (MPF-BCQI) Algorithm with Best CQI Consideration for LTE-A Networks - Ibraheem, Mai Ali; ElShennawy, Nada; Sarhan, Amany Mahmoud (2018 13th International Conference on Computer Engineering and Systems (ICCES), 2018)
Quality of Service (QoS) requirements, such as fairness, average throughput and spectral efficiency, are a set of the important parameters that assess the performance of scheduling algorithms. LTE-Advanced (LTE-A) is the most viable wireless broadband network that strongly supports QoS by using Admission Control (AC) and Packet Scheduling (PS). In LTE-A, Proportional Fair (PF) scheduling algorithm and its modified versions have proved to be the commonly used scheduling algorithms for their ability to provide fairness while Best Channel Quality Indicator (CQI) scheduling algorithm guarantees high throughput. In this paper, we propose a new scheduling algorithm by considering a tradeoff balance between throughput and fairness among users by combining Best CQI and PF schedulers' metrics. Moreover, we enhance the PF scheduler performance using new averaging methods namely; median, range and geometric mean for computing the average throughput which is further used to determine the scheduling priority. The performance evaluation is presented using Vienna system level simulator. The results reveal that the performance of the proposed scheduler, with the new averaging methods in PF, gives better performance than the compared to schedulers in terms of throughput, fairness and spectral efficiency.